Analisis Perbandingan Model Altman Z-Score, Springate dan Grover dalam Memprediksi Kebangkrutan pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Ananda Putri Kusuma Dewi; Dian Anita Sari (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Using a variety of bankruptcy prediction models, this research examines company insolvency using ratio computations in financial statements. The objective of this research is to identify the best effective model for bankruptcy analysis by comparing and contrasting the Altman Z-Score, Springate, and Grover models for forecasting insolvency in banking organizations listed on the Indonesia Stock Exchange. This quantitative analysis relies on secondary data collected from the Indonesia Stock Exchange's yearly banks financial reports covering the years 2020–2024. Using a purposive sampling technique, 45 financial institutions were included in the final tally. As part of the data analysis process, tests for normality, one-way ANOVA Kruskal Wallis, and accuracy were conducted. In sum, the study found that the Altman Z-Score, Springate, and Grover models vary significantly from one another and the Grover model had the best accuracy in predicting the insolvency of banking companies listed on the Indonesia Stock Exchange for the period 2020–2024, beating out the Altman Z-Score and Springate models.